2017
DOI: 10.1038/s41467-017-01391-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporally separated cortical flows and spindle geometry establish physical asymmetry in fly neural stem cells

Abstract: Asymmetric cell division, creating sibling cells with distinct developmental potentials, can be manifested in sibling cell size asymmetry. This form of physical asymmetry occurs in several metazoan cells, but the underlying mechanisms and function are incompletely understood. Here we use Drosophila neural stem cells to elucidate the mechanisms involved in physical asymmetry establishment. We show that Myosin relocalizes to the cleavage furrow via two distinct cortical Myosin flows: at anaphase onset, a polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 66 publications
(89 reference statements)
12
89
0
Order By: Relevance
“…Since the wide field data were not sufficiently reliable to extract Myosin intensity, we imaged third instar neuroblasts expressing Sqh::GFP with spinning disc microscopy and correlated the resulting intensity and curvature profiles with AFM stiffness data by calculating the relative change between Myosin and curvature, and Myosin and stiffness. As reported previously (Roubinet et al, 2017), apical Myosin intensity started to decrease at anaphase onset, albeit stiffness increased again apically. In the mid and sub-basal region, both Myosin intensity and stiffness increased.…”
Section: Neuroblast Stiffness Is a Combination Of Actomyosin Contractsupporting
confidence: 87%
See 2 more Smart Citations
“…Since the wide field data were not sufficiently reliable to extract Myosin intensity, we imaged third instar neuroblasts expressing Sqh::GFP with spinning disc microscopy and correlated the resulting intensity and curvature profiles with AFM stiffness data by calculating the relative change between Myosin and curvature, and Myosin and stiffness. As reported previously (Roubinet et al, 2017), apical Myosin intensity started to decrease at anaphase onset, albeit stiffness increased again apically. In the mid and sub-basal region, both Myosin intensity and stiffness increased.…”
Section: Neuroblast Stiffness Is a Combination Of Actomyosin Contractsupporting
confidence: 87%
“…The most noticeable curvature changes became apparent in the furrow region from 120s after anaphase onset onwards ( Figure 1E,F,G). The resulting deviation coefficients revealed that Myosin intensity and curvature strongly correlate on the early (-120 -30s) apical neuroblast cortex and later in the cleavage furrow region (120s -240s); the shift in Myosin intensity from the apical cell cortex towards the furrow region -previously described as a cortical flow (Roubinet et al, 2017) was accompanied with a shift in curvature changes. Until 120s after anaphase onset, stiffness correlated best with Myosin intensity in the cleavage furrow region.…”
Section: Neuroblast Stiffness Is a Combination Of Actomyosin Contractmentioning
confidence: 88%
See 1 more Smart Citation
“…The promotion of spindle asymmetry in 1:0 cells would in this case represent an excessive reaction of such a feedback system. Alternatively, in naturally asymmetric spindles (Delaunay et al, 2014;Greenan et al, 2010;Ren and Weisblat, 2006;Roubinet et al, 2017), HURP asymmetry could reinforce the spindle asymmetry by freezing the dynamics of the shorter k-fibers, and thus promote asymmetric cell divisions. This potential function of HURP was not only visible in 1:0 cells, but also in 0:0 cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rotational flow emerges after formation of cell-cell contacts, where contact-dependent asymmetries determine cortical flow dynamics, which in turn determine spindle orientation through coupling to microtubule dynamics (Sugioka and Bowerman, 2018). These roles of cortical flow in patterning are orthologous in higher organisms, where they have been shown to drive decision making processes in development (Woolner and Papalopulu, 2012;Maitre et al, 2016;Roubinet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%